Analysis of the Potential Structure of the Economic Sector of North Kalimantan Province Before and After Regional Expansion - Marshelynda, Alfia Rahmadhanti; Taufiq, M.; Wardaya, Wirya (Indonesian Journal Publisher, 2026)
This study aims to analyze the economic potential, sector contribution, competitiveness level, and economic classification in five regions—Malinau, Bulungan, Tana Tidung, Nunukan, and Tarakan City—in the period before (2007–2011) and after the expansion (2013–2017). The research approach is quantitative descriptive by utilizing secondary data analyzed using the Location Quotient (LQ), Shift Share (SS), and Klassen Typology methods. The results of the study show that there is a shift in the base sector from the two main sectors, namely mining and processing industry, to five leading sectors after expansion, namely agriculture, forestry, and fisheries; construction; transportation and warehousing; and government administration. Although the contribution of the mining sector decreased after expansion, it still plays a major role in the regional economy. Regional competitiveness shows an increase, especially in the agricultural sector and government administration. The regional economic structure has also undergone a transformation from the dominance of extractive activities to diversification in the construction, transportation, information technology, and service sectors. Based on the Klassen Typology classification, there has been an increase in the number of post-expansion leading sectors which reflects a stronger and more sustainable direction of economic development.